Solid phase extraction of Cu (II), Ni (II), Co (II), and Fe (III) ions in water samples using salicylaldehyde benzoylhydrazone on Amberlite XAD-4 and their determinations by flame atomic absorption spectrometry - Alpdogan, Guzin (TAYLOR & FRANCIS LTD, 2016)
A multi element preconcentration procedure for solid phase extraction on Amberlite XAD-4 as their salicylaldehyde benzoylhydrazone chelates and flame atomic absorption spectrometric determination of some trace metal ions in water samples are proposed in this work. The influences of some analytical parameters, including pH of aqueous solution, amounts of reagent, flow rates of sample and eluent solutions, and sample volume on the quantitative recoveries of copper, nickel, cobalt, and iron were investigated. The effects of concomitant ions on the retentions of the analytes were also examined. The developed method has been successfully applied to the determination of metal ions in some real samples, including, tap water, river water, spring water, and waste water.
Keywords: solid phase extraction; Amberlite XAD-4; salicylaldehyde benzoylhydrazone; preconcentration; FAAS; HEAVY-METALS; ONLINE PRECONCENTRATION; RESIN; SYSTEM; COPPER; LEAD; CADMIUM; BIOSORPTION; ZINC; AAS; Environmental Sciences & Ecology; Toxicology